Ações de grupos sobre polinômios irredutíveis - Daniela Alves de Oliveira (2019)
Let n be a positive integer and let F_{q^n} be the finite field with q^n elements, where q is a prime power. The aim of this work is to study a natural action of the Projective Semilinear Group PΓL(2,q^n) = PGL(2,q^n)xGal(F_{q^n}/F_q) on the set of irreducible monic polynomials over the finite field F_{q^n}. Our main results concern the characterization and number of fixed points of this action.